The effect of polypropylene fibers in different lengths on some properties of heat-cured acrylic resin processed by autoclave (Mustansiria Dental Journal, 2018)
Background: some properties of heat-cured acrylic resin are required to beimproved (like flexural strength, hardness and porosity) by adding different types offibers like polypropylene fiber, also needed to determine these properties withaddition of polypropylene fibers and curing the polymer by autoclave. The aim of thisstudy was to evaluate the effect of adding polypropylene fibers in two differentlengths (6mm, 12mm) and concentration 2%, and the effect of autoclave processingon some properties(flexural, surface hardness and porosity).Material and method: A total No. of 120 specimens were prepared in this studyand divided into two main groups according to length of fibers (6mm,12mm) , eachmain group was subdivided into two groups according to method of adding the fiber(directly to the powder or immersed in monomer). Each group of them contain 10specimens for each test.Result: in this study, the transverse strength and surface hardness of heat curedacrylic reinforced by randomly oriented polypropylene fibers (12mm, 2%) regardlessto application method with higher significance than other groups. Fiber reinforcementand autoclave processing showed non-significant effect on porosity of heat cureacrylic resin according to ANOVA t-test.Conclusion: Reinforcement by randomly oriented polypropylene fiber (12mm,2%) added with and without immersion in monomer better than other groupsaccording to transverse strength and surface hardness with autoclave processing butthere is no effect of added fibers on porosity test.